Isolated finger flexor vs. exhaustive whole-body climbing tests? How to assess endurance in sport climbers? - Baláš, J., Gajdošík, J., Giles, D.; Fryer, S.; Krupková, D.; Brtník, T.; Feldmann, A. (European Journal of Applied Physiology, 2021)
Purpose: Sport climbing requires high-intensity finger flexor contractions, along with a substantial whole-body systemic oxygen uptake (V.O2) contribution. Although fatigue is often localised to the finger flexors, the role of systemic V.O2 and local aerobic mechanisms in climbing performance remains unclear. As such, the primary purpose of this study was to determine systemic and local muscle oxygen responses during both isolated finger flexion and incremental exhaustive whole-body climbing tests. The secondary aim was to determine the relationship of isolated and whole-body climbing endurance tests to climbing ability. Methods: Twenty-two male sport climbers completed a series of isometric sustained and intermittent forearm flexor contractions, and an exhaustive climbing test with progressive steepening of the wall angle on a motorised climbing ergometer. Systemic V.O2 and flexor digitorum profundus oxygen saturation (StO2) were recorded using portable metabolic analyser and near-infra red spectroscopy, respectively. Results: Muscle oxygenation breakpoint (MOB) was identifiable during an incremental exhaustive climbing test with progressive increases in angle (82 ± 8% and 88 ± 8% V.O2 and heart rate climbing peak). The peak angle from whole-body treadwall test and impulse from isolated hangboard endurance tests were interrelated (R2 = 0.58-0.64). Peak climbing angle together with mean V.O2 and StO2 from submaximal climbing explained 83% of variance in self-reported climbing ability. Conclusions: Both systemic and muscle oxygen kinetics determine climbing-specific endurance. Exhaustive climbing and isolated finger flexion endurance tests are interrelated and suitable to assess climbing-specific endurance. An exhaustive climbing test with progressive wall angle allows determination of the MOB.